Neurosensory analysis of tooth sensitivity during at-home dental bleaching: a randomized clinical trial (Journal of Applied Oral Science, 2022)
Objective: The objective of this study was to evaluate dental sensitivity using visual analogue scale, a Computerized Visual Analogue Scale (CoVAS) and a neurosensory analyzer (TSA II) during at-home bleaching with 10% carbamide peroxide, with and without potassium oxalate. Materials and Methods:Power Bleaching 10% containing potassium oxalate was used on one maxillary hemi-arch of the 25 volunteers, and Opalescence 10% was used on the opposite hemi-arch. Bleaching agents were used daily for 3 weeks. Analysis was performed before treatment, 24 hours later, 7, 14, and 21 days after the start of the treatment, and 7 days after its conclusion. The spontaneous tooth sensitivity was evaluated using the visual analogue scale and the sensitivity caused by a continuous 0°C stimulus was analyzed using CoVAS. The cold sensation threshold was also analyzed using the TSA II. The temperatures obtained were statistically analyzed using ANOVA and Tukey's test (α=5%). Results: The data obtained with the other methods were also analyzed. 24 hours, 7 and 14 days before the beginning of the treatment, over 20% of the teeth presented spontaneous sensitivity, the normal condition was restored after the end of the treatment. Regarding the cold sensation temperatures, both products sensitized the teeth (p<0.05) and no differences were detected between the products in each period (p>0.05). In addition, when they were compared using CoVAS, Power Bleaching caused the highest levels of sensitivity in all study periods, with the exception of the 14th day of treatment. Conclusion: We concluded that the bleaching treatment sensitized the teeth and the product with potassium oxalate was not able to modulate tooth sensitivity.